Inflation targeting and product market deregulation - Laura Moretti (Goethe University Frankfurt, Center for Financial Studies (CFS), 2012)
I evaluate the effect of inflation targeting on inflation and how it interacts with product market deregulation during the disinflationary process in the 1990s. Using a sample of 21 OECD countries, I show that, after controlling for product market deregulation, the effect of inflation targeting is quantitatively important and statistically significant. Moreover, product market deregulation also matters in particular in countries that adopted an inflation targeting regime. I propose a New Keynesian Phillips curve with an explicit role for market deregulation to rationalize the empirical evidence.
urn:nbn:de:hebis:30:3-241164
Keywords: E31; E58; E65; L51; 330; Inflation Targeting; Product Market Deregulation; Difference in Difference; Inflation Targeting; Produkt; Markt; Deregulierung; New-Keynesian Phillips Curve; Schätzung; OECD-Staaten